Measuring the efficiency of public schools in Uruguay: Main drivers and policy implications - Daniel Santín; Gabriela Sicilia (Latin American Economic Review, 2015)
The aim of this research is to explore the existence of inefficient behaviors in public high schools in Uruguay and identify its potential drivers. To do so, we perform a two-stage model using PISA 2009 and 2012 databases. In the first stage, we use Data Envelopment Analysis (DEA) to estimate efficiency scores, which are then regressed on school and student contextual variables. This second stage is carried out using four alternative models: a conventional censored regression and three different regression models based on the use of bootstrapping recently proposed in the literature. Our results show that educational efficiency in Uruguayan high schools significantly dropped in nine percentage points between 2009 and 2012. In terms of educational policy recommendations, in order to reduce the inefficiencies in the evaluated public schools in Uruguay, the focus should be put on reducing grade-retention levels and promoting teaching-learning techniques that enhance student's mathematics study skills and assessing students continuously through test and homework throughout the academic year. In this vein, our findings also show positive effects on public schools' efficiency of providing the responsibility in the distribution of the school budget to school principals.
Keywords: I21; C14; H52; 330; Public secondary education; Technical efficiency; Performance-based reforms; PISA; DEA